Vogelmädchen - O'Dell, Scott 1898-1989 (Dt. Taschenbuch-Verl., 1992)
A young Indian woman, accompanied by her infant and cruel husband, experiences joy and heartbreak when she joins the Lewis and Clark Expedition seeking a way to the Pacific.
Keywords: Sacagawea -- Fiction; Sacagawea -- Juvenile fiction; Lewis and Clark Expedition -- (1804-1806) -- Fiction; Geschichte 1804; Indianer; Indians of North America -- Fiction; Kultur; Weiße; Expedition; Nordamerika; Jugendbuch